Influence of squeegee impact on stencil printing process: CFD approach. Issue 1 (October 2020) - Ishak, M.H.H.; Abdul Aziz, M.S.; Abdul Samad, M.H.S.; Ismail, Farzad; Mohd Salleh, M.A.A
Abstract: This work has been conducted to predict the real time observation of solder paste Sn96.5Ag3.0Cu0.5 (SAC305) filling process into stencil apertures as well as print quality in stencil printing by using Computational Fluid Dynamics (CFD) approach. A 3-Dimensional stencil printing model was developed and simulated in FLUENT by using different squeegee parameters which are the angle and printing speed. An experimental work was performed to be compared with part of the simulation results in term of print quality for validation purpose. It is found that squeegee angle 60° to 80° has potential to obtain good print quality of solder paste. In addition, print speed range between 35 mm/s to 95 mm/s also can be the good print speed option to achieve good print quality in stencil printing process. Finally, the maximum pressure distribution of solder paste also changes substantially as the squeegee travel further with respect to different values of tested parameters.